Difference in the Faecal Elastase-1 Concentration between Resectable and Unresectable Pancreatic Cancer - Abdul Rahman M; Marcellus Simadibrata; Irsan Hasan; Suhendro Suhendro; E Mudjadid (The Indonesian Society for Digestive Endoscopy, 2020)
Background: In the pancreatic cancer can occur pancreatic exocrine insufficiency (PEI) that can be detected by measurement of fecal elastase-1 level. The aim of this study was to identify the proportion and the degree of PEI, proportion of steatorrhea in pancreatic cancer, the concentration difference of faecal elastase-1 between resectable and unresectable pancreatic cancer and mean concentration difference of faecal elastase-1 based on the stage of pancreatic cancer.Method: This was a cross-sectional study to determine the concentration difference of faecal elastase-1 between resectable and unresectable pancreatic cancer. This research was conducted at Cipto Mangunkusumo hospital, several network hospitals of Cipto Mangunkusumo hospital, and Wahidin Sudirohusodo Makasar hospital from November 2014 until May 2015. The statistical test used to assess differences in the levels of faecal elastase-1 between resectable and unresectable pancreatic cancer was Mann Whitney and Kruskal Wallis test was performed to assess the differences between the mean levels of faecal elastase 1 based on staging pancreatic cancer.Results: A total of 48 subjects with pancreatic cancer participated in this study, with resectable category was 19 (39.6%) subjects, and 29 (60.4%) subjects were unresectable. The proportion of patients with pancreatic cancer who experienced PEI was 75% (CI 95% 0.63 - 0.87) and the proportion of patients with pancreatic cancer who showed steatorrhea symptoms was 68.8% (CI 95% 0.557 - 0.819). There was no significant difference of faecal elastase-1 levels (P = 0.738) between the resectable and unresectable whereas the resectable group median value was 38.0 (15-500) μg/g and in unresectable group was 35.0 (15-500) μg /g. There was no significant difference (p = 0.767) in faecal elastase-1 levels based on the stage of pancreatic cancer with median (range) in stage IB 36 (15-100) pg/g, stage IIA 62 (15-500) pg/g, stage III 15 (15-500) μg/g, and stage IV 36 (15-500) μg/g.Conclusion: This study found a high proportion of PEI and steatorrhea in pancreatic cancer. There was no significant difference in faecal elastase-1 levels between the resectable and unresectable pancreatic cancer. There was no significant difference between mean levels of faecal elastase-1 based on the stage of pancreatic cancer.